Endocrine Disruption in the European Eel, Anguilla anguilla, Exposed to an Environmental Cocaine Concentration - GAY, FLAMINIA; VALIANTE, Salvatore; LAFORGIA, VINCENZA; CAPALDO, ANNA; Maddaloni M (Water, Air, & Soil Pollution, 2013)
The aim of the present study was to verify if cocaine, at environmental concentrations, influences the endocrine system of the European eel. Silver eels (a stage of the eel life cycle preparing the fish for the oceanic reproductive migration) were exposed to a nominal cocaine concentration of 20 ng/l during thirty days; at the same time, control, carrier and post-exposure recovery groups were made. The effects of cocaine were observed in 1) brain dopamine content 2) plasma catecholamine levels: dopamine, norepinephrine and epinephrine 3) pituitary-adrenal axis activity: plasma adrenocorticotropic hormone (ACTH), corticosterone, cortisol and aldosterone levels 4) pituitary-thyroid axis activity: plasma thyroid-stimulating hormone (TSH), triiodothyronine and thyroxine levels. In the treated group, brain dopamine, plasma catecholamines, cortisol and TSH levels were higher, whereas ACTH, corticosterone and triiodothyronine levels were lower than controls. In the post-exposure recovery group, brain dopamine, plasma dopamine and epinephrine, and thyroxine levels further increased, whereas plasma norepinephrine, cortisol and corticosterone levels were similar to treated values. Finally, ACTH and TSH were similar, whereas triiodothyronine levels were lower than controls. Aldosterone levels were unaffected by cocaine exposure. The results of the present study show that cocaine, at environmental concentrations, behaves like an endocrine disruptor changing brain dopamine and plasma catecholamine levels, and the activity of pituitary-adrenal/thyroid axes. Since the endocrine system plays a key role in the metabolic and reproductive processes of the eel, our results suggest that environmental cocaine could be considered another cause for the decline in the European eel.